Knowledge, empathy, and willingness to counsel patients with HIV among Indonesian pharmacists: a national survey of stigma. Issue 1 (2nd January 2022) - Sianturi, E. I.; Latifah, E.; Pane, M.; Perwitasari, D. A.; Satibi,; Kristina, S. A.; Hastuti, E. B.; Pavlovich, J.; Taxis, K.
ABSTRACT: This study aimed to assess the level of HIV treatment knowledge, empathy, and HIV stigma of pharmacy students and pharmacists working with patients as well as potential factors associated with stigma. This survey included 250 hospital pharmacists within 33 provinces and 1013 final-year pharmacy students from Java, the most populated island in Indonesia. The data were collected via Qualtrics® and distributed by WhatsApp. The mean age of the participants was (Mean ± SD) 24.68 ± 5.30 years, and 80.0% were female. The mean knowledge score of students and pharmacists were 14.14 ± 2.01 and 15.39 ± 1.87, respectively, out of the maximum score of 21. The mean empathy score of students and pharmacists was 72.06 ± 5.39 and 77.40 ± 1.35, respectively out of the maximum score of 105. The mean stigma score of students and pharmacists was 21.02 ± 4.65 and 20.66 ± 4.41, respectively, out of a maximum score of 48. Regression analysis showed that knowledge, empathy, and willingness to counsel patients were negatively associated with stigma. Working with patients was positively associated with stigma. A multi-level intervention including education may reduce stigma and strengthen the role of pharmacists in caring for patients.